PEMANFAATAN TWITTER API UNTUK MENGAKSES JADWAL BIMBINGAN DOSEN PADA IST AKPRIND YOGYAKARTA - La Ode Malik Hasan; Muhammad Sholeh; Catur Iswahyudi (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Twitter is a social networking that is booming today because it can interact with other users via computer or mobile devices. Twitter users consists of various background. Based on the field survey results at the Institute of Science and Technology AKPRIND, to perform guidance, students should look for lecturers and sometimes the student is difficult to meet with the supervisor due to the schedule of teaching and outside learning activities, so that the guidance is not reach expectations and student guidance schedule. According to survey results, how to connect between social media twitter and information systems, where twitter as an interface for the student to send the data, while the system information as a receiver, collecting and managing the data sent from twitter. This research was conducted by combining the technology of mobile phones, social networking twitter and information system based on PHP, MySQL, and Web Service with implemented Crontab technology and API (Application Programming Interface). By using mobile phones and social networking twitter as an interface, while the information system as a receiver, collector and organize the data can be easily understood by its user, implementation of crontab application on this system can help providing quick response to any incoming mention.Tests carried out using a desktop browser and mobile browser that aims to test and observe the performance of applications on crontab, and observed the responses sent from the system back to twitter. After testing, a response back using crontab with a minimum of 1 minute run in accordance with the specified time, so that the guidance schedule data retrieval process faster, but do not overload the system functional.